New records of the River Shark Glyphis (Carcharhinidae) reported from Cape York Peninsula, northern Australia - Peverell, S. C.; Mcpherson, G. R.; Garrett, R. N.; Gribble, N. A. (Zootaxa, 2006)
The distribution of the river shark Glyphis in northern Australia is extended with new records of occurrence in the Gulf of Carpentaria and a reassessment of historical survey data from Cape York Peninsula. Nine new specimens of Glyphis sp. A were collected in 2005 from the Weipa region on the Queensland coast of the Gulf of Carpentaria. A re-examination of archival records from 1978–86 marine and estuarine fish surveys in the Gulf of Carpentaria and along the northern Queensland East Coast allowed a further nineteen Glyphis specimens to be identified. Combined this gives twenty-eight new records of Glyphis specimens from the coasts of Cape York Peninsula, Queensland. Common habitat characteristics for all captures were turbid, shallow, fast running tidal water in the upper reaches of coastal rivers. The substrate was generally muddy and the rivers lined with mangrove. In all surveys the representation of Glyphis was low, being less than 1% of the total shark captures historically and 0.002 sharks 50 m net hour -1 in Weipa 2005. The size range captured was 1000–1800 mm total length historically and 705 –1200 mm total length from Weipa 2005, with none recorded as sexually mature. Diagnostic characteristics of the Weipa specimens, identified as Glyphis sp. A, were: lower jaw teeth protruding and “spear-like”; second dorsal fin greater than half the height of the first dorsal fin; the snout relatively short and fleshy in the lateral view; pectoral fin ventral surface black in colouration; the precaudal vertebral count between 118 and 123; and the total vertebral count between 204 and 209.